(untitled) (PUSA Journal of Hospitality and Applied Sciences, 2016)
Background: Tourism is a social, cultural and economic phenomenon which entails the movement of people to countries or places outside their usual environment for personal or business/ professional purposes. Tourism helps to assimilate culture and social bondage. Theme parks and amusement parks are very good tourist attractions. An amusement park is a combination of thrill rides, roller coaster rides, family rides, water attractions or rides in darkness in a covered train. Chail, a tourist destination in H.P is one of the popular tourist destinations. Opening an amusement park will help to attract more tourists. Objective: To identify the feasibility of opening a Amusement park in Chail, H.P. Methodology: The research instrument used was a questionnaire was 30 tourists visiting Chail. Results: Around 86% of the tourist population agreed that provision of Amusement Park would give opportunity to development of Chail and of the state overall. 76% agreed Amusement Park will be a value addition to Chail and help in the economic and financial upliftment of the state. Conclusion: Value addition of Amusement Park in tourist places would help in social and cultural development of the state. Such leisure activity acts as strong magnet for tourism industry.